Numerical Investigation of the Effects of Impurity on CO2 Sequestration in Stratified Formation. (May 2017) - Li, Didi; Jiang, Xi
Abstract: Numerical simulations are performed to investigate the effects of N2 or H2 S impurity on CO2 geological storage in stratified formations. The results reveal that the horizontal migration distance of the CO2 plume increases with increasing N2 concentrations but decreases with increasing H2 S concentrations. Furthermore, the CO2 plume containing higher N2 concentrations tends to experience larger buoyancy and thus there are more gases accumulating under the caprock. The distribution range of the CO2 plume is larger when N2 concentration is higher in the injected CO2 stream, which means that the interaction area between the CO2 plume and the formation brine is also larger. As a result, dissolved CO2 mass in the formation brine increases with increasing N2 concentrations. With increasing H2 S contents, however, dissolved CO2 mass decreases due to decreasing two-phase zone. With the same injection rate, dissolved CO2 ratio increases with increasing N2 concentrations. On the other hand, different H2 S concentrations in the injected CO2 streams do not cause noticeable changes in the dissolved CO2 percentage. At the same impurity mole fraction, the effect of N2 is much stronger than that of H2 S, partially because H2 S at the leading edge has preferentially dissolved in the formation brine.